Nisin ZP Combined with Limited Chemotherapy in Oropharyngeal Squamous Cell Carcinoma: A Case Report - Ye, Qianlin; He, Aimin; Wu, Yeping; Kapila, Yvonne L (Archives of Clinical and Medical Case Reports, 2024)
Objective: This case report describes and discusses the therapeutic potential of nisin ZP as adjunctive therapy in patients with oral squamous cell carcinoma (OSCC). Case Report: A 43-year-old Asian male with OSCC initiated treatment with Paclitaxel and Cisplatin chemotherapy. Nisin ZP was administrated during and after the chemotherapy. Results: The patient experienced symptom relief and significant tumor regression following administration of nisin ZP. Conclusion: Nisin ZP shows promising potential as an adjunctive therapy for OSCC, offering symptom relief and contributing to tumor size reduction.